SINERGITAS KINERJA GURU PAI DAN PENGAWAS DALAM MENINGKATKAN KUALITAS PEMBELAJARAN SMP DI KOTA AMBON PROVINSI MALUKU - Rosdiana Rosdiana (EDUCANDUM, 2018)
This study aims to reveal the proportion, synergy of performance, supportingand inhibiting factors in the implementation the main tasks and functions of thePAI teacher and supervisors. Quantitative research with this survey approachwas explored using questionnaires, interviews, documentation to capture datarelating to performance of PAI teachers and supervisors and then synchronizethem to find synergy of performance of both. The data obtained is used todescribe the characteristics synergy of performance PAI teachers andsupervisors. The results of the study found that the proportion PAI teachers andsupervisors was very lacking and had not shown balance. The level ofsupervision provided by supervisors is related to the performance of PAIteachers and supervisors high categorized. The level of quality is very lowshown in the aspect of research and development, likewise the synergy ofperformance produced by PAI teachers and supervisors is very highcategorized. The results synergistic analysis between the two were interpretedeven though it was very high but the mastery of PAI teachers and supervisorstowards the research methodology seemed low. Supporting and inhibitorsfactors the quality supervision of PAI teachers, support related toadministration,school components, and school facilities when carrying outsupervision tasks. Constraints in carrying out supervisory tasks include the number of teachers and madrasas, transportation, participation in educationand training, ATK and funds, distance of schools / madrasas, and readiness ofteachers when supervised. While for the teacher, supporting the PAI teacher'stask is more to the facilitation aspects of the learning process (students,principals and parents) and the constraints faced by some PAI teachers in usingthe learning facility curriculum, and the intensity of supervisor visits